Neutron residual stress measurement and numerical modeling in a curved thin-walled structure by laser powder bed fusion additive manufacturing. (5th December 2017) - An, Ke; Yuan, Lang; Dial, Laura; Spinelli, Ian; Stoica, Alexandru D.; Gao, Yan
Abstract: Severe residual stresses in metal parts made by laser powder bed fusion additive manufacturing processes (LPBFAM) can cause both distortion and cracking during the fabrication processes. Limited data is currently available for both iterating through process conditions and design, and in particular, for validating numerical models to accelerate process certification. In this work, residual stresses of a curved thin-walled structure, made of Ni-based superalloy Inconel 625™ and fabricated by LPBFAM, were resolved by neutron diffraction without measuring the stress-free lattices along both the build and the transverse directions. The stresses of the entire part during fabrication and after cooling down were predicted by a simplified layer-by-layer finite element based numerical model. The simulated and measured stresses were found in good quantitative agreement. The validated simplified simulation methodology will allow to assess residual stresses in more complex structures and to significantly reduce manufacturing cycle time. Graphical abstract: Neutron is a powerful tool for residual stress determination in AM structures. Highlights: Experimentally solving residual stress of curved structure without stress free lattice measurement Accelerated stress simulation for additively manufacturing by simplified methodology Validated methodology can be easily adapted to complex parts for guiding part geometry design and process parameter design.